Large Specific Surface Area Macroporous Nanocast LaFe1−xNixO3: A Stable Catalyst for Catalytic Methane Dry Reforming - Chunfeng Chen; Zhaojun Meng; Zijun Wang (Journal of Chemistry)
Macroporous nanocast perovskites, LaFe1−xNixO3 (x = 0.3, 0.5, and 0.7), were synthesized by using a nanocasting technique with SBA-15 as a template and applied to methane dry reforming (MDR). The prepared catalysts were characterized by X-ray diffraction, transmission electron microscopy, specific-surface-area analysis, hydrogen temperature-programmed reduction, and thermogravimetric analysis. LaFe1−xNixO3 revealed a large specific surface area, which could enhance its catalytic activity. The catalysts were reduced to Ni/LaFeO3-La2O3 in the MDR reaction. The alkaline additive, La2O3, and perovskite oxide, LaFeO3, strongly interacted with the active component to reduce the surface energy of metal particles and prevent aggregation of active Ni. The results showed that LaFe0.5Ni0.5O3 and LaFe0.3Ni0.7O3 perform better than LaFe0.7Ni0.3O3. More importantly, LaFe0.5Ni0.5O3 had a very long lifetime (>80 h) in the MDR reaction. The LaFe0.5Ni0.5O3 catalyst showed excellent stability in the MDR reaction and has potential use in industrial applications.